Enterprise Risk Management Disclosure in Automotive Companies: A Comparative Analysis in Indonesia and Malaysia - Shiddiq, Muhammad Fajryan; Kristanti, Farida Titik (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
Enterprise Risk Management Disclosure (ERMD) is an integral part of corporate governance that supports transparency and risk management. This study aims to compare risk management disclosure factors in Indonesian and Malaysian automotive companies from 2014 to 2023. The results show that the level of risk management disclosure increased significantly in both countries, with Indonesia experiencing more significant growth than Malaysia. Audit committee effectiveness and firm size positively influenced risk disclosure, while leverage and capital intensity showed a negative influence. Overall, risk management disclosures are influenced by internal firm factors and regulatory differences in the two countries. Firms with strong oversight and large size are more likely to disclose risks transparently. The findings provide important insights for regulators, investors, and academics to enhance risk disclosure and support better corporate governance in the ASEAN region.